La «Theologia Crucis» de Lutero (Scripta Theologica, 2018)
The author analises the principle concepts which Luther makes use of in order to layout his theologia crucis. He starts out with the famous visibilia et posteriora Dei of the Debate in Heildelberg in 1518, theses 19 and 20, and carefully examines all of Luther's literary patrimony rigbt from his first works in 1509. From this analisis the author deduces: a) that Luther's great theses on justification, the sola fides, the turning away from the Papacy, etc., have their ultimate root and are in a way determined in Luther's cristology; b) that this cristology shows a fundamental misunderstanding of the tradition of cristological and trinitary faith as defined by the Councils; e) that the reading of Luther's theses has been carried out in later centuries throught Melanchton, who toned them down from their own fundamentally orthodox cristology, and this has made Luther's own stand go unrevealed; d) that Luther's great options in the decisive cristological questions are already found in the works he wrote from 1509 to 1511, much earlier than the «crisis» that would later set of the Protestant Reform. e) that at the root of these options there isn't primarly an analisis of the biblical texts, but the influence of the philosophical outlook of the Pseudo-Hermes Trismegisto and of the mystisism of Theologia Deutch. The author ends off by contrasting Luther's theologia crucis with the one Adriana von Speyr and Edith Stein lived.